The First Ones Back: Actor Testimony and the ‘Show Must Go On’ Ethos at the Stratford Festival of Canada in 2021 - Lane, Cyrus (Université d'Ottawa / University of Ottawa, 2024)
This thesis looks at Shakespearean performance at the Stratford Festival of Canada during its 2021 outdoor ‘pandemic’ season. It argues that the dominant pre-pandemic ‘show must go on’ ethos, that puts institutional well-being ahead of actor well-being, persisted during the pandemic season, even as the Festival implemented painstaking anti-racist and anti-oppressive initiatives. Alongside this argument, the thesis interrogates the ethics around the use of actor testimony in scholarship and attempts to ethically expand its focus from pure Shakespearean performance to include actor statements on institutional practices and policy. Extensive interviews with the 2021 casts of A Midsummer Night’s Dream and R+J are, to this end, at the heart of the study. The paper follows Bridget Escolme’s instruction to use actor testimony dialogically and places these interviews in conversation with contemporary Shakespearean performance theory around labour, disability, diversity, pandemic Shakespeare, the nature of the ‘Shakespearean actor’ in Western culture, and, most importantly, with actor testimony from other sources and the auto-ethnography of the author, a Stratford actor himself. Concentrating on testimony around Zoom, masking, and social distancing during the rehearsal process, the thesis reveals the emotional, physical and financial difficulties the actors took on in order for the show to go on at the Stratford Festival during the Covid-19 pandemic.
Keywords: actor; Pandemic Shakespeare; Shakespeare; Shakespearean Performance pandemic; Covid 19; Stratford Festival